2018
DOI: 10.3892/mmr.2018.8535
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis-associated protein 2 promotes the metastasis of non-small cell lung carcinoma by regulating the ERK/AKT and VEGF signaling pathways

Abstract: Non-small cell lung carcinoma (NSCLC) is the most common cause of cancer-associated mortality in the world and accounts for ~85% of human lung cancers. Metastasis-associated protein 2 (MTA2) is a component of the histone deacetylase complex and serves a role in tumor progression; however, the mechanism through which MTA2 is involved in the progression of NSCLC remains unclear. The aim of the present study was to investigate the expression and function of MTA2 and the MTA2-mediated signaling pathway in NSCLC ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…Downregulation of MTA2 through the suppression of both the PI3K/AKT and MAPK/ERK pathways ultimately leads to the inhibition of breast tumor growth 32. Silencing MTA2 inhibits the invasive potential of NSCLC cells through the ERK/AKT and VEGF signaling pathways 33. In the present study, the inhibitory effect of MTA2 knockdown on the migration and invasion of HCC cells by inactivating the p38MAPK signaling pathway was confirmed.…”
Section: Discussionsupporting
confidence: 69%
“…Downregulation of MTA2 through the suppression of both the PI3K/AKT and MAPK/ERK pathways ultimately leads to the inhibition of breast tumor growth 32. Silencing MTA2 inhibits the invasive potential of NSCLC cells through the ERK/AKT and VEGF signaling pathways 33. In the present study, the inhibitory effect of MTA2 knockdown on the migration and invasion of HCC cells by inactivating the p38MAPK signaling pathway was confirmed.…”
Section: Discussionsupporting
confidence: 69%
“…That vascular endothelial growth factor (VEGF)‐mediated angiogenesis has a vital role in tumor‐associated metastasis is widely accepted . Several studies have reported that VEGF molecules are critical components in the pathogenesis of non‐small‐cell lung cancer (NSCLC) cells . Clinical studies have demonstrated that serum VEGF levels and tumor size (and microvessel density) are significantly correlated in patients with NSCLC .…”
Section: Introductionmentioning
confidence: 99%
“…The potential target of MEQ, MTA2, as one nonenzymatic subunit in the NuRD complex, confers functional specificity for the NuRD complex by associating with different transcription factors or targeting distinct gene loci 50 . Moreover, MTA2 is found to be overexpressed in human breast cancer 51 , and the VEGF signaling pathway was able to be modulated by targeting MTA2 expression in non small cell lung cancer cells 52 . Thus, characterizing drugs that target NuRD subunits for cancer therapy should be more specific and effective than those targeting pan-epigenetic modification enzymes.…”
Section: Discussionmentioning
confidence: 99%